A Modified Novel Validated High-Throughput Hemagglutinin Inhibition Assay Using Recombinant Virus-like Particles and Human Red Blood Cells for the Objective Evaluation of Recombinant Hemagglutinin Nanoparticle Seasonal Influenza Vaccine - Timothy S. Vincent; Mingzhu Zhu; Anand Parekh; Urvashi Patel; Shane Cloney-Clark; Andrew Klindworth; David Silva; Andrew Gorinson; Karlee Miranda; Mi Wang; Zachary Longacre; Bin Zhou; et al. (Microorganisms)
Currently available seasonal influenza vaccines confer variable protection due to antigenic changes resulting from the accumulation of diverse mutations. The analysis of new seasonal influenza vaccines is challenging in part due to the limitations of the traditional hemagglutination inhibition (HAI) assay with A/H3N2 strains. An improved and objective novel HAI assay was developed with recombinant virus-like particles (VLPs) and an egg-derived virus as agglutinins, the oseltamivir treatment of VLPs, human red blood cells, and using an automated image reader-based analysis of hemagglutination. HAI validation was demonstrated using four VLPs and egg-derived strains, with 46–56 serum samples tested 12 times in duplicate per strain. The validated HAI assay was precise as indicated by the percent geometric coefficient of variation for intra-, inter-, and total assay precision, as well as accurate as evidenced by percent bias measurements. The assay exhibited linearity, specificity for homologous type/subtype strains, and sensitivity with a starting dilution of 1:10. Assay robustness and sample stability were demonstrated as a percentage difference compared to reference condition. Validated HAI results were equivalent for the single and duplicate sample testing and correlated well with a qualified live wild-type influenza microneutralization assay. These findings demonstrate the suitability of this high-throughput novel modified validated HAI assay for evaluating vaccine immunogenicity and efficacy.